PEMETAAN PATOLOGI BIROKRASI DALAM PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) DI KOTA MAKASSAR - Ismaniar Ismail; Novayanti Sopia Rukmana S (Jurnal Ilmiah Administrasita', 2018)
Bureaucratic pathology is a picture of the deviations that occur in the process of organizing government. The main problem in this article is to map the forms of pathology that occur Izin Mendirikan Bangunan (IMB) in Makassar City. This studyuses qualitative. Data collection is done through collecting, interviewing and documenting informants who are directly involved in the research. The process of data analysis adds data reduction, data presentation, and completes conclusions. Theresults showed the pathology that occurred in the Izin Mendirikan Bangunan (IMB), namely (1) the inhibition of changes, creativity and innovation in the daily life of the bureaucracy as a result of the lack of budget provided and associated with overlapping relationships, and (2 ) between bureaucracies so that there is importance in work. This is due to poorly coordinated communication between DPMPTSP and Dinas Tata Ruang in Makassar City.